Evaluation of six different airway devices regarding regurgitation and pulmonary aspiration during cardio-pulmonary resuscitation (CPR) – A human cadaver pilot study. (May 2016) - Piegeler, Tobias; Roessler, Bernard; Goliasch, Georg; Fischer, Henrik; Schlaepfer, Martin; Lang, Susanna; Ruetzler, Kurt
Abstract: Background: Chest compressions and ventilation are lifesaving tasks during cardio-pulmonary resuscitation (CPR). Besides oxygenation, endotracheal intubation (ETI) during CPR is performed to avoid aspiration of gastric contents. If intubation is difficult or impossible, supraglottic airway devices are utilized. We tested six different airway devices regarding their potential to protect against regurgitation and aspiration during CPR in a randomized experimental human cadaver study. Methods: Five-hundred ml of 0.01% methylene-blue-solution were instilled into the stomach of 30 adult human cadavers via an oro-gastric tube. The cadavers were then randomly assigned to one of six groups, resulting in 5 cadavers in each group. Airway management was performed with either bag-valve ventilation, Laryngeal Tube, EasyTube, Laryngeal Mask (Classic), I-Gel, or ETI. Thereafter 5 min of CPR were performed according to the 2010 Guidelines of the European Resuscitation Council. Pulmonary aspiration was defined as the presence of methylene-blue-solution below the vocal cords or the ETI cuff as assessed by fiber-optic bronchoscopy. Results: Thirty cadavers were included (14 females, 16 males). Aspiration was detected in three out of five cadavers receiving bag-valve ventilation and in two out of five intubated with LMA or I-Gel. In cadavers intubated with the LT, aspiration occurred in one out of five cases. No aspiration could be detected in cadavers intubated with ETI and EasyTube. Conclusion: This study provides experimental evidence that, during CPR, ETI offers superior protection against regurgitation and pulmonary aspiration of gastric contents than supraglottic airway devices or bag-valve ventilation.